EKSTRAK UMBI GADUNG, Dioscorea hispida DENNST AKSESI TIMOR LESTE SEBAGAI ZAT ANTI MAKAN BAGI WALANG SANGIT, Leptocorisa oratorius F. (HEMIPTERA: ALYDIDAE), HAMA TANAMAN PADI, Oryza sativa L. - , ELISIO DA SILVA NETO ([Yogyakarta] : Universitas Gadjah Mada, 2012)
d Rice bug (Leptocorisa oratorius F.) cause lost of rice grain yield reached 10-40%, even 100% lost of rice grain. Insecticide extrated from plants have been developed to control rice bug recently. Water extracts yam tubers (Dioscorea hispida Dennst) has been used as an insecticide by some rice farmers in Timor Leste. This study has two aims, the first was to determine the effectiveness of yam tubers extracted by water, metanol, and chloroform respectively, as antifeedant for rice bug. The Second one was to analyze the compounds of extracting product. The study was conducted from Marh to May 2012 at the Entomology Laboratory and Biochemistry labortory, Faculty of Biology UGM. Extract of tubers yam produced by macerating of 150g powder yam tubers with methanol, chloroform, and water respectively. There were two series of bioassay, 5% and 10% series. Each series consist of water, metanol, and chloroform extract respectively. The treatments withs three times replication. Each series of concentration treated to rice plants and its exposed to 30 imago of rice bug. All treatmets was done in the three arms olfactometer. Analyzing of the compound extracts by Thin Layer Chromatography (TLC). indicated that only between 2,22% The results -7,78% rice bug choosed the paddy with tubers extract, while between 75,56%-76,67% rice bug chooced paddy without tubers extract. Its meant yam tubers extracts were effective as antifeedant for rice bug. There were four classed compounds of the yam tubers extracts, alkaloids, saponins, terpenoids, and phenolic.